1982
DOI: 10.1139/b82-043
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface wax in susceptibility of plants to air pollutant injury

Abstract: The relationship between quantity of epicuticular wax and plant sensitivity to hydrogen chloride (HCl) gas was investigated using 8-, 12-, and 16-day-old Phaseolus vulgaris L. plants exposed for 20 min to 27.6 2 3.9 mg ~~l . m -~.Twelve-day-old plants were more sensitive than 8-or 16-day-old plants and possessed the lowest mean surface wax quantity. Multiple regression analysis showed that surface wax quantity was negatively linearly related to percent of leaves glazed. Necrotic injury was also negatively corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As no significant interaction between ozone and acid mist was shown in the present study, it is concluded that the combined effects of the pollutants on the wettability of the needle surface are no more than additive. Increased wettability of the needle surfaces induced by ozone and/or acid mist may enhance foliar leaching (Tukey, 1971), aid pollutant uptake from the atmosphere (Swiecki, Endress & Taylor, 1982), increase susceptibility to phylloplane pathogens (Rotem, 1978) and exacerbate the physical effects of frost (Barnes et al, 1988a).…”
Section: Discussionmentioning
confidence: 99%
“…As no significant interaction between ozone and acid mist was shown in the present study, it is concluded that the combined effects of the pollutants on the wettability of the needle surface are no more than additive. Increased wettability of the needle surfaces induced by ozone and/or acid mist may enhance foliar leaching (Tukey, 1971), aid pollutant uptake from the atmosphere (Swiecki, Endress & Taylor, 1982), increase susceptibility to phylloplane pathogens (Rotem, 1978) and exacerbate the physical effects of frost (Barnes et al, 1988a).…”
Section: Discussionmentioning
confidence: 99%
“…(Huttunen & Laine, 1983;Riding & Percy, 1985;Crossley & Fowler, 1986). The amount of epicuticular wax on leaflets of pinto bean {Phaseolus vulgaris L.) exposed to gaseous hydrogen chloride was negatively correlated with the degree of foliar injury (Sweicki, Endress & Taylor, 1982). Fumigation with SOg stimulated wax production in ryegrass (Lolium perenne L.) (Koziol & Cowling, 1981), but such effects were later found to be dependent upon genotype, SOg concentration and season (Shelvey & Koziol, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations, however, schJer 1971), exchange of gases with the atmosphere show no or only poor correJations between cuticular (Jeffree et al 1971), protection against mechanical and transpiration and the quantity of epicuticular lipids pest damage (Martin 1964), and protection against ul- (Denna 1970a,b, Rama Das et al 1979. In addition to traviolet radiation (Clark and Lister 1975) and air pol-the total amount, other properties of the epicuticular Klutants (Swiecki et al 1982). Despite the potential sig-pids, such as different components or different chain nificance of these aspects, experimental evidence for lengths of these, might affect the water loss through the specific functions is tacking.…”
Section: Introductionmentioning
confidence: 99%